D-serine released by astrocytes in brainstem regulates breathing response to CO2 levels. Issue 1 (December 2017) - Beltrán-Castillo, S.; Olivares, M.; Contreras, R.; Zúñiga, G.; Llona, I.; von Bernhardi, R.; Eugenín, J.
Abstract Central chemoreception is essential for adjusting breathing to physiological demands, and for maintaining CO2 and pH homeostasis in the brain. CO2 -induced ATP release from brainstem astrocytes stimulates breathing. NMDA receptor (NMDAR) antagonism reduces the CO2 -induced hyperventilation by unknown mechanisms. Here we show that astrocytes in the mouse caudal medullary brainstem can synthesize, store, and released -serine, an agonist for the glycine-binding site of the NMDAR, in response to elevated CO2 levels. We show that systemic and raphe nucleusd -serine administration to awake, unrestrained mice increases the respiratory frequency. Application ofd -serine to brainstem slices also increases respiratory frequency, which was prevented by NMDAR blockade. Inhibition ofd -serine synthesis, enzymatic degradation ofd -serine, or the sodium fluoroacetate-induced impairment of astrocyte functions decrease the basal respiratory frequency and the CO2 -induced respiratory response in vivo and in vitro. Our findings suggest that astrocytic release ofd -serine may account for the glutamatergic contribution to central chemoreception. Astrocytes are involved in chemoreception in brainstem areas that regulate breathing rhythm, and astrocytes are known to released -serine. Here the authors show that astrocyte release ofd -serine contributes to CO2 sensing and breathing in brainstem slices, and in vivo in awake unrestrained mice.